Comparative morphological, karyological and palynological investigations of three endemic Centaurea L. species (Asteraceae) in Turkey - Hayta, Sukru; Tasar, Neslihan; Kiran, Yasar; Baser, Birol (Taylor & Francis Ltd, 2017)
Centaurea derderiifolia Wagenitz., Centaurea drabifolia Sm. subsp. floccosa (Boiss.) Wagenitz & Greuter and Centaurea kotschyi (Boiss. & Heldr.) Hayek var. floccosa (Boiss.) Wagenitz, which are endemic taxa from Turkey belonging to Centaurea sect. Cheirolepis, were subjected to morphological, karyological and palynological investigations. The somatic chromosome numbers, pollen morphology and detailed morphometric properties were examined. The somatic chromosome numbers were determined as 2n = 2x = 36 in C. derderiifolia, C. kotschyi var. floccosa, and C. drabifolia subsp. floccosa. Karyotype analysis indicated that chromosomes of these Centaurea taxa generally have median region (m), submedian region (sm) and rarely median point (M) karyotypes. The pollen morphology of these endemic taxa of the genus Centaurea was investigated by light and scanning electron microscopy. The pollen grains of the examined species are mainly isopolar and radially symmetric, subprolate, tricolporate. Tectum ornamentation is scabrate and scabrate-perforate, amb triangular. The pollen grains of all taxa studied are 3-zonocolporate. The colpus is usually long, acute at ends and with smooth membrane. Pollen grains belonging to Cheirolepis section reveal homogeneity in their characters.
Keywords: Chromosome; Centaurea; Cheirolepis; pollen; Turkey